Derrida and our animal others : Derrida's final seminar, "The beast and the sovereign" - Krell, David Farrell (Studies in Continental thought., 2013)
Jacques Derrida's final seminars were devoted to animal life and political sovereignty - the connection being that animals slavishly adhere to the law while kings and gods tower above it, and that this relationship reveals much about humanity in the West. Here, the author offers a detailed account of these seminars, placing them in the context of Derrida's late work and his critique of Heidegger. The author focuses his discussion on questions such as death, language, and animality.